2009
DOI: 10.1007/s10495-008-0302-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of apoptosis in cardiovascular disease

Abstract: Apoptosis plays a key role in the pathogenesis in a variety of cardiovascular diseases due to loss of terminally differentiated cardiac myocytes. Cardiac myocytes undergoing apoptosis have been identified in tissue samples from patients suffering from myocardial infarction, diabetic cardiomyopathy, and end-stage congestive heart failure. Apoptosis is a highly regulated program of cell death and can be mediated by death receptors in the plasma membrane, as well as the mitochondria and the endoplasmic reticulum.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
209
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 301 publications
(219 citation statements)
references
References 150 publications
(157 reference statements)
6
209
0
4
Order By: Relevance
“…In cardiac myocytes, mitochondria constitute about 30% of cell volume to ensure efficient ATP supply for the contracting myocyte. 18 As shown by staining for Cytochrome c Oxidase subunit IV (COX IV), mitochondria were very abundant in control infected myocytes (Fig. 2C).…”
Section: Discussionmentioning
confidence: 83%
“…In cardiac myocytes, mitochondria constitute about 30% of cell volume to ensure efficient ATP supply for the contracting myocyte. 18 As shown by staining for Cytochrome c Oxidase subunit IV (COX IV), mitochondria were very abundant in control infected myocytes (Fig. 2C).…”
Section: Discussionmentioning
confidence: 83%
“…It has been proved that the PI3K/Akt signaling pathway was critical in ischemic defense and pharmacologic preconditioning of cardioprotection (Qiao et al, 2016). In order to be cardioprotective and prevent the development of heart failure, the damage of myocardial cells could be lowered via inhibiting the apoptosis process (Lee and Gustafsson, 2009). Studies also revealed that part of the mechanisms of protecting cardiomyocytes relied on the activity of Akt, which can activate the downstream spot targets, improve energy generation of mitochondria, and then decrease the pro-apoptotic factors (Tong et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…To better elucidate the interplay between ER stress and oxidative stress in ER stress-induced cardiac responses, ROS production, protein damage, apoptosis, mitochondrial integrity including mitochondrial membrane potential and mitochondrial permeation pore (mPTP) opening, as well as cell signaling of Akt and GSK3b were scrutinized in wild-type (WT) and transgenic mice with intrinsic Akt activation after ER stress induction. Levels of caspase-8 and pro-caspase-9 were assessed to evaluate the role of receptor and mitochondrial death domains, respectively (15). In addition, expression of caspase-12, an ER-specific member of the caspase family to mediate ERspecific apoptosis (28), was also monitored under ER stress and chronic Akt activation.…”
Section: Introductionmentioning
confidence: 99%